1975
DOI: 10.1080/00039896.1975.10666674
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Neuromuscular Disorder in Methylmercury Poisoning

Abstract: Data suggestive of a neuromuscular disorder responsive to neostigmine was uncovered in the course of electrophysiological testing of Iraqi patients poisoned by methylmercury. Subsequent neostigmine therapy produced a remarkable clinical improvement of the patients. Placebo substitution resulted in a substantial loss of testable strength that was restored when drug therapy was resumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

1976
1976
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 13 publications
1
10
0
1
Order By: Relevance
“…In the Iraqi episode of poisoning, ~14% of the patients presented with a neuromuscular weakness resembling myasthenia gravis; its origin was not determined Bakir et al, 1980), nor was a definitive diagnosis of myasthenia gravis made. Motor dysfunction in MeHg-poisoned humans includes ataxia, muscle weakness, and inability to walk; these observations are consistent with clinical signs of neuromuscular-like disorders, suggesting that MeHg impacts MN function to some extent (Eto, 1997, Eto et al, 2002; Dietrich et al, 2005, Rustam et al, 1975). Additionally, MN-directed disease, including amyotrophic lateral sclerosis, has been reported after exposure to inorganic Hg (Adams et al, 1983; Praline et al, 2007; Rooney, 2011).…”
Section: Effects Of Mehg On Motor Efferentssupporting
confidence: 69%
“…In the Iraqi episode of poisoning, ~14% of the patients presented with a neuromuscular weakness resembling myasthenia gravis; its origin was not determined Bakir et al, 1980), nor was a definitive diagnosis of myasthenia gravis made. Motor dysfunction in MeHg-poisoned humans includes ataxia, muscle weakness, and inability to walk; these observations are consistent with clinical signs of neuromuscular-like disorders, suggesting that MeHg impacts MN function to some extent (Eto, 1997, Eto et al, 2002; Dietrich et al, 2005, Rustam et al, 1975). Additionally, MN-directed disease, including amyotrophic lateral sclerosis, has been reported after exposure to inorganic Hg (Adams et al, 1983; Praline et al, 2007; Rooney, 2011).…”
Section: Effects Of Mehg On Motor Efferentssupporting
confidence: 69%
“…The inhibition of muscarinic receptor binding induced by in vivo exposure to cadmium is similar to that seen by parallel in vitro studies (Hedlund et al 1979). In addition, the concentrations of lead and mercury that are effective in inhibiting muscarinic receptors in vitro approximate those which occur in metal poisoning of the brain (Rustam et al 1975;Aronstam and Eldefrawi 1979). However, in one study, lead-treated animals have been found to exhibit no changes in the level of the striatal dopamine receptor (Govoni et al 1979).…”
Section: Discussionmentioning
confidence: 96%
“…The toxic effects of lead and mercury are especially pronounced at the neurological level (Felton et al 1972;Rustam et al 1975). The tremor, poor coordination and other movement disturbances caused by compounds containing these heavy metals, suggested that they may in part exert their effects by way of interference with nerve function.…”
Section: Introductionmentioning
confidence: 99%
“…The manifestations in vivo of massive chronic mercury poisoning are often conspicuous. It is known that high concentrations of methyl-Hg (5 pM) in vivo can exert toxic actions on excitable tissue (20). However, during distribution of small amounts of mercury, effects that are less pronounced than those associated with acute and massive chronic poisoning could be exerted on tissues in the body.…”
mentioning
confidence: 98%